EXTRACTING LAND USE CHANGING USING MORPHOLOGICAL CHANGING APPROACH IN THE PUTIH RIVER BODIES IN JUMOYO, SALAMAN, MAGELANG, CENTRAL JAVA (CASE STUDY: PRE AND POST ERUPTION OF MERAPI VOLCANO) - Rini Meiarti, at al (Departmen Teknik Geologi, 2015)
This research focuses on providing information related to the damaging effects of the 2010 eruption of Merapi volcano in Central Java, Indonesia. This information will be used to help emergency responders to assess losses more timely and efficiently, and to monitor the progress in emergency response and recovery. The objectives of this research are: (a) to generate a map of pyroclastic deposits based on activities pre- and post-volcano eruption of 2010 in the research area, (b) to investigate the impact of volcano eruption on the environment, and (c) to assess the impact of volcano eruption on landuse. Google earth remote sensing data pre- and post-disaster were used in this research for mapping the volcano eruption. Topographic and geomorphological maps were analyzed for profiling and field orientation, which were used to investigate the impact of volcano eruption on the environment. GOOGLE EARTH satellite images were used in this research for updating land use information from the topographic map. The result of the land use updated data was used for assessment of the volcano eruption’s impact on land use with the GIS raster environment. The volcanic eruption that occurred in 2010 is estimated to have an impact of 133.31 ha for settlements, 92.32 ha for paddy fields, 235.60 ha for dry farming, 570.98 ha for plantations, 380.86 ha for bare land, and 0.12 ha for forest areas. An estimate of the number of buildings damaged due to the volcano eruption in 2010 was carried out by overlaying a map of pyroclastic deposits and the information point of the building sites from the topographic map. The total number of buildings damaged is estimated to be around 12,276 units.